RNA-based analyses reveal fungal communities structured by a senescence gradient in the moss Dicranum scoparium and the presence of putative multi-trophic fungi - Chen, Ko-Hsuan (The New phytologist, 2018)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.